Quality of life improvement in HIV-1 patients treated with raltegravir in a real-life observational study: RACING. Issue 1 (2nd January 2017) - Spire, Bruno; Nait-Ighil, Lella; Pugliese, Pascal; Poizot-Martin, Isabelle; Jullien, Vincent; Marcelin, Anne-Geneviève; Billaud, Eric
Abstract : Background : Good efficacy and safety of raltegravir in person living with HIV was demonstrated in clinical trials over five years, but real-life data, particularly about quality of life (QoL), are lacking. QoL was evaluated over time in adult patients first treated or switched to regimens containing raltegravir in an observational cohort study. Methods : Patient QoL was evaluated using the Fatigue Impact Scale (FIS) and the HIV Symptom Index (HSI). Data were collected at baseline and at 1, 3, 6, 12, 18, and 24 months. Baseline FIS and HSI subscores were compared with the scores at each visit using the paired Wilcoxon test. The impact of time, sociodemographic and medical variables upon patient-perceived fatigue and symptoms was also assessed using mixed multivariate models. Results : From baseline, all FIS and HSI subscores improved significantly after one month of treatment. In addition, psychosocial FIS subscores and both the frequency of bothersome symptoms and HSI subscores improved significantly at each visit. Physical FIS subscores also improved significantly, except at month 18, whereas both cognitive and total FIS subscores improved only after 6 months and 24 months, respectively. In multivariate analysis, employment was independently associated over time with improved improvement in both FIS and HSI subscores. Conclusion : Patient QoL improved significantly over a 24-month period of treatment with a raltegravir-containing regimen. FIS and HSI are sensitive tools to measure the impact of new antiretroviral combinations on a patient's perception of QoL.